Society and culture - Ebia, Erlito Vegerano Salvador (Philippines; Mindsapers, Co.Inc., 2016)
Sociology understands as society's norms, values, and beliefs; as well as its objects and symbols, and the meaning given to those objects and symbols. A culture represents the beliefs and practices of a group, while society represents the people who share those beliefs and practices.
English Text
Keywords: Sociology